Human bone morphogenetic protein-2 (hBMP-2) characterization by physical–chemical, immunological and biological assays - Suzuki, Miriam Fussae; Oliveira, João Ezequiel; Damiani, Renata; Lima, Eliana Rosa; Amaral, Kleicy Cavalcante; Santos, Anderson Maikon de Souza [UNESP]; Magalhães, Geraldo Santana; Faverani, Leonardo Perez [UNESP]; Pereira, Luis Antonio Violin Dias; Silva, Fabiana Medeiros; Bartolini, Paolo (Springer Nature, 2020)
Commercially available preparations of methionyl-human BMP-2 and CHO-derived hBMP-2, which belongs to the transforming growth factor β (TGF-β) superfamily, were used for a complete characterization. This protein is an extremely efficient osteoinductor that plays an important role during bone regeneration and embryonic development. Characterization was carried out via SDS-PAGE and Western blotting, followed by reversed-phase HPLC, size-exclusion HPLC and MALDI-TOF-MS. The classical in vitro bioassay, based on the induction of alkaline phosphatase activity in C2C12 cells, confirmed that hBMP-2 biological activity is mostly related to the dimeric form, being ~ 4-fold higher for the CHO-derived glycosylated form when compared with the E. coli counterpart. The E. coli-derived met-hBMP-2 has shown, by MALDI-TOF-MS, a large presence of the bioactive dimer. A more complex molecular mass (MM) distribution was found for the CHO-derived product, whose exact MM has never been reported because of its variable glycosylation. A method based on RP-HPLC was set up, allowing a quantitative and qualitative hBMP-2 determination even directly on ongoing culture media. Considering that hBMP-2 is highly unstable, presenting moreover an extremely high aggregate value, we believe that these data pave the way to a necessary characterization of this important factor when synthesized by DNA recombinant techniques in different types of hosts.
Keywords: BMP-2; C2C12 bioassay; CHO cell-derived; Efficient osteoinductor; Escherichia coli-derived